Association between Neighborhood-Level Smoking and Individual Smoking Risk: Maternal Smoking among Latina Women in Pennsylvania. (November 2015) - Chesnokova, Arina; French, Benjamin; Weibe, Douglas; Camenga, Deepa R.; Yun, Katherine
Objective: We examined whether or not high maternal smoking rates at the neighborhood level increase the likelihood of individual smoking by Latina women in the three months prior to and during pregnancy, independent of other individual and neighborhood factors. Methods: This study was observational in nature, using linked vital statistics records for 24, 443 Latina women in Pennsylvania (2009–2010) and U.S. Census data for 2, 398 census tracts. We used multilevel logistic regression models to determine the individual odds of self-reported maternal smoking given different census tract-level rates of maternal smoking in the previous three years (2006–2008), adjusting for maternal and census-tract characteristics, including ethnic density, population density, and poverty. Results: Higher levels of maternal smoking at the census-tract level were associated with increased individual odds of smoking among Latina mothers. In the fully adjusted model, a 10% increase in the neighborhood smoking rate was associated with a 1.28 (95% confidence interval 1.22, 1.34) increase in the individual odds of smoking. Conclusion: Latina women living in census tracts where more women have smoked during or immediately prior to pregnancy are themselves at higher risk of smoking during this period.